Compliance of Radiotherapy Treatment at a Tertiary Cancer Center in India—A Clinical Audit - Khanna, Nehal R.; Kumar, Anuj; Kataki, Kaushik; Sehra, Nishtha; Laskar, Sarbani Ghosh; Mummudi, Naveen; Gupta, Tejpal; Tibdewal, Anil; Pathak, Rima; Wadasadawala, Tabassum; Krishnatry, Rahul; Chopra, Supriya; Goda, Jayant Sastri; Chatterjee, Abhishek; Budrukkar, Ashwini; Gurram, Lavanya; Engineer, Reena; Murthy, Vedang; Swain, Monali; Laskar, Siddhartha; Sarin, Rajiv; Agarwal, Jai Prakash (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Noncompliance to planned radiotherapy (RT) treatment is associated with inferior outcomes and also serves as an indicator of quality of care offered to the patients. Identification of the rate of noncompliance and its causative factors can help us develop an insight toward implementing mitigation measures thereby improving the quality of treatment.Objective To ascertain the incidence of noncompliance and the factors affecting the same in patients offered RT appointments.Materials and Methods We retrospectively reviewed the records of patients from January 1, 2019, to December 31, 2019, who were noncompliant (defaulted RT simulation or defaulted initiation of RT or defaulted planned RT during the course of RT but excluding planned/unplanned treatment breaks or early conclusions prescribed by the treating radiation oncologist) for the planned RT treatment.Results Of the 8,607 appointments (7,699 external beam RT and 908 brachytherapy) given to the patients attending the radiation oncology outpatient department in the year 2019, a total of 197 (2.28%) patients were found to be noncomplaint. Ninety-seven patients defaulted RT simulation (49.2%), 53 defaulted RT starting (26.9%), and 47 defaulted while on RT (23.9%). Half of these had either head–neck (29.9%) or gynecological (20.8%) malignancies. Patients with breast cancers had the least noncompliance rates (0.02%). The cause for noncompliance was ascertained in 135 patients (68.5%). The common causes of noncompliance were the desire to continue treatment closer to home (21.5%) followed by logistic (17%), lack of confidence in the curative potential of the planned therapy (17%), and financial reasons (11.8%). Patients with head–neck and gynecological malignancies were more often with advanced staged disease and were planned multimodal treatment protocols. The majority of the 23 patients who defaulted palliative RT were planned for fractionated treatments (73.9%).Conclusion The incidence of noncompliance in patients planned for RT in our institute can be considered optimum. Appropriate counseling of patients at the time of scheduling appointment, upfront identification of patients at high risk of noncompliance, and assisting patients with financial and logistic challenges are imperative to ensure adherence to planned treatment schedule.
Keywords: compliance; external beam; radiotherapy